Karakterisasi Zat Warna Kayu Secang (Caesalpinia sappan L.) Fraksi Kloroform:Metanol sebagai Photosensitizer pada Dye Sensitized Solar Cell - Suriadi; Aisyah; Suriani; Ibrahim Patunrengi, Iswadi (Al-Kimia, 2025)
The electricity crisis in Indonesia is caused by the decreasing supply of fossil fuels for power plants. One solution to overcome this problem is the Dye-sensitized Solar Cell (DSSC) which can convert sunlight into electrical energy by utilizing environmentally friendly organic dyes. This study has succeeded in making and determining DSSC using organic dyes derived from sappanwood extract with pH variations (4, 7, and 10). Each pH level produces efficiency values ​​of 0.01714%, 0.05497% and 0.03174%. VLC with a chloroform: methanol ratio (5:5 and 1:9) was then characterized using UV-Vis, FTIR, and GC-MS instruments. Characterization of sappanwood dye extract using UV-Vis instrument showed absorption at wavelengths of 243, 285, 445, and 541. FTIR instrument provided information on functional groups –OH at wave number 3415.93 cm-1 and C-O-C at wave number 1255.66 cm-1 which are characteristic of isoflavonoid compounds. In addition, GC-MS instrument indicated the possibility of fragment m/z 286 at retention time 9.54 is a brazilin